Implementation of Competency-Based Curriculum in Bandung Natural School - Destiwati, Rita; Harahap, Junardi (EDUCARE, 2013)
ABSTRACT: Competency-Based Curriculum is a new curriculum in Indonesia; it is as perfecting of curriculum before. The KBK (Kurikulum Berbasis Kompetensi or Competency-Based Curriculum) mission is unifying curriculum that can touch whole aspects of children needed, one to each other is related; it is not separation but it can also reflect to skill dimension with interested theme. Meanwhile, at this time, the development of children creativity is determined by the closeness of teachers, one is determined by the applicable curriculum. In the field, the problems have also been faced by both principals or managers and teachers or educators regarding KBK socialization issues. This research tries to answer about how the implementasion of competency-based curriculum in Bandung Natural School generally as well as specifically? The research uses qualitative method through descriptive approach, observation, deep interview, and library study. The outcome of this research shows that set up of communication in KBK application at Bandung Natural School is more based on autonomy in written form and non-written; the process of communication in KBK application at Bandung Natural School is the best collaboration between theory of Â learning in the class with adventure and exploration on the nature; media of communication that is used on Bandung Natural School is hand-phone, e-mail, letter, michrophone, publishing, and connecting book; and the supporting factor is the qualities of teacher, while the inhibiting factor is being act of challenging as taking care of children problem. KEY WORDS: Competency-based curriculum, media, teacher and student, professional skill, and Bandung Natural School.Â Â About the Authors: Rita Destiwati, M.Si. is an English Lecturer at the Telkom Polytechnic, Jalan Telekomunikasi, Terusan Buah Batu, Bandung, West Java, Indonesia; and Junardi Harahap, M.Si. is a Lecturer at the Department of Anthropology, Faculty of Political and Social Sciences UNPAD (Padjadjaran University), Jalan Raya Bandung-Sumedang Km.21, Jatinangor, West Java, Indonesia. The authors can be contacted via e-mail at: ritadestiwati@gmail.com and junardi_harahap@unpad.ac.idHow to cite this article? Destiwati, Rita & Junardi Harahap. (2013). âImplementation of Competency-Based Curriculum in Bandung Natural Schoolâ in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.27-34. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 25, 2013); Revised (July 29, 2013); and Published (August 17, 2013).Â Â